Evaluation of different cooling management strategies for lactating Holstein × Gir dairy cows - Lourenço, João Paulo De A [UNESP]; Cappellozza, Bruno I; Bertin, Rafaela D [UNESP]; Miranda, Victor F. B [UNESP]; Junior, Wilson M. C [UNESP]; De Sousa, Osvaldo A [UNESP]; Vasconcelos, José Luiz M [UNESP] (My University, 2021)
Heat stress negatively impacts production, reproduction, and health of ruminants and strategies to alleviate these losses are warranted. Therefore, four experiments evaluated different cooling strategies on vaginal temperature (VT) of Holstein × Gir cows. Experiment 1 compared different amounts of water (2-or 4-L) over a 1-hour period from 1000 to 1100 h and 1600 to 1700 h. Experiment 2 evaluated the effects of sprinkling duration (in hours; 1-or 2-H), whereas Experiment 3 evaluated the effects of water amount (4-or 8-L) applied for 1-or 2-H. Lastly, the effects of a cooling strategy on specific hours of the day, starting at either 0700 (T-1) or 1100 h (T-2; Experiment 4), were evaluated. In all experiments, 12 Holstein × Gir cows were used in a 2 × 2 Latin Square Design containing two periods of 6 days each. Temperature and humidity index (THI) were recorded hourly and VT was recorded every 10-min throughout the experiments. As expected, an hour effect was observed for THI (P < 0.0001), which peaked early in the afternoon. In Experiment 1, a treatment × hour interaction was observed (P < 0.0001) for VT, as animals assigned to receive 4-L had a reduced VT at 1100, 1600, 1700, and 2300 h (P ≤ 0.03). During the cooling applications, cows receiving 4-L for 1 h had a reduced VT from 60 to 150 min (P ≤ 0.04). In Experiment 2, a treatment × hour interaction was observed (P < 0.0001) for VT, as animals assigned to receive 4-L of water for 2-H had a reduced VT at 1200 h (P = 0.05). Moreover, during the cooling process, VT was reduced for 2-H cows from 140 to 170 min after the beginning of the cooling process (P ≤ 0.05). In Experiment 3, animals assigned to receive 4-L + 2H had a reduced VT at 1200, 1700, 1800, and 1900 h (P < 0.001). A treatment × hour interaction was observed (P < 0.0001), as VT was reduced for 4-L + 2-H cows from 130 to 180 min after the beginning of the cooling process (P ≤ 0.05). In Experiment 4, by the time when the first cooling cycle of T-1 was applied (0700 h), T-1 cows consistently had (P ≤ 0.05) a reduced VT up to the hottest hours and greatest THI of the day (1400 and 1500 h). This pattern was maintained until the end of the last cooling cycle, whereas T-2 cows had a reduced VT. In summary, 4 L of water over a 5-min cycle for a period of 2 hours twice a day maintained VT of Holstein × Gir cows at lower levels. Moreover, the hour at which the first cooling cycle starts also should be considered when evaluating the efficacy of a cooling strategy for an entire day.
Keywords: cooling management; dairy cows; heat stress; temperature-humidity index; vaginal temperature